Pengaruh Kualitas Pelayanan, Persepsi Harga dan Kualitas Produk terhadap Kepuasan Pelanggan untuk Meningkatkan Loyalitas Pelanggan di Hotel The Westin Jakarta - Yahya Saipuloh; Surono Surono (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study aims to determine and analyze the effect of service quality, perceived price and product quality on customer satisfaction to increase customer loyalty at The Westin Jakarta hotel. The population in this study are customers who stay 2 times or more at The Westin Jakarta hotel. The number of samples in this study were 100 respondents. Data collection using a questionnaire. The research method used in quantitative research methods. The analytical method uses PLS. The results showed that service quality, price perceptions and product quality had a positive effect on customer satisfaction. Customer satisfaction has a positive effect on customer loyalty at The Westin Jakarta hotel. The test results show an NFI value of 0.728 so that the research model is 72.8% fit. The R-Square value for customer satisfaction is 0.456 which means that 45.6% of customer satisfaction is influenced by service quality, perceived price and product quality. The R-Square value for customer loyalty is 0.165 which means that 16.5% of customer loyalty is influenced by customer satisfaction.